(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
This study shows to what extent treatment with Ziziphus mauri tiana Lam can ameliorate the hazards induced by exposing animals to EMW with a frequency of 950 MHz and 4 Gy single dose of gamma ionizing radiation in serum and liver tissue. Rats were segregated into six groups control, EMW, whole body γ- irradiation, EMW followed by γ- irradiation and EMW followed by Ziziphus extract then exposed to γ- irradiation groups. Irradiation with 4 Gy γ- rays significantly increased the levels of serum Alpha-Fetoprotein (AFP), Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) activities; with substantial reductions in liver glutathione peroxidase (GPx), while lipid peroxides as malondialdehyde (MDA), nitric oxide (NO), Heat Shock Protein 70 (HSP 70), Nuclear Factor κB (NFkB) and tumor suppressor protein (P53) levels significantly increased in liver tissue after EMW or ionizing radiation exposure. However, these effects became marked in all parameters in Group 5 as compared either to Group 3 or 4. Interestingly, among the tested parameters, ziziphus extract showed significant recovery in the previous biochemical parameters. Ziziphus extract is effective antioxi dants and could be attenuate oxidative damages caused by electromag netic and ionizing radiation.